Antimicrobial cytotoxicity and phytochemical activities of Spilanthes acmella (Bangladesh Journal of Scientific and Industrial Research, 2013)
?-Sitosterone was isolated from the dichloromethane extract of the leaves of Spilanthes acmella. Stigmasterol was isolated from the petroleum and dichloromethane extract respectively. The structures of compounds were elucidated on the basis of spectral analysis as well as by comparison with available literature data. Pet-ether & DCM extract and two column fractions of DCM and one pure compound were subjected to antimicrobial screening & brine shrimp lethality. All of the fractions showed moderate to strong inhibitory activity to microbial growth. On the other hand, the pet ether extract and pure compound (stigmasterol) showed strongest cytotoxicity having LC50 1.2 ?g/mL and 2.02 ?g/mL respectively. Bangladesh J. Sci. Ind. Res. 47(4), 437-440, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14073